Volumetric analysis after caries excavation with caries detecting dyes and chemomechanical caries removal agents using 3D scanner-a randomised clinical trial - Roja Bastia; Shashirekha Govind; Ali A. Assiry; Noura Abdulaziz Alessa; Mohammed Abdul Kader; Adbul Habeeb Adil; Mohmed Isaqali Karobari (BMC, 2024)
Abstract Aim This research aimed to use an extra-oral 3D scanner for conducting volumetric analysis after caries excavation using caries-detecting dyes and chemomechanical caries removal agents in individuals with occlusal and proximal carious lesions. Methods Patients with occlusal (A1, A2, A3) and proximal carious lesions (B1, B2, B3) were treated with the conventional rotary technique, caries detecting dyes (CDD) and chemomechanical caries removal (CMCR) method on 90 teeth (n = 45 for each). Group A1, B1: Excavation was performed using diamond points. Group A2, B2: CDD (Sable Seek™ caries indicator, Ultradent) was applied and left for 10 s, and then the cavity was rinsed and dried. For caries removal, diamond points or excavators were used. Group A3 and B3: BRIX3000 papain gel was applied with a micro-brush for 20 s and was activated for 2 min, and then the carious tissue was removed with a sharp spoon excavator. Post-excavation cavity volume analysis was performed using a 3D scanner. The time required and the verbal pain score (VPS) for pain were scored during excavation. Post-restoration evaluation was performed at 1, 3, and 6 months FDI (Federation Dentaire Internationale) criteria. Results Comparison of age, time and volume with study groups were made using Independent Sample' t' test and one-way analysis of variance (ANOVA) for two and more than two groups, respectively. Using Cohen's Kappa Statistics, evaluators 1 and 2 agreed on caries removal status aesthetic, functional and biological properties at different follow-ups. The chi-square test revealed that the rotary groups [A1(2.5 ± 0.4 min) B1(4.0 ± 0.4 min)] had significantly less (p = 0.000) mean procedural time than CDD [A2(4.5 ± 0.4 min) B2(5.7 ± 0.4 min)] and CMCR [A3(5.4 ± 0.7 min) B3(6.2 ± 0.6 min)] groups. The CMCR group showed better patient acceptance and less pain during caries excavation than the rotary and CDD groups. CMCR group showed significantly less mean caries excavated volume(p = 0.000). Evaluation of restoration after 1-, 3-, and 6-month intervals was acceptable for all the groups. Conclusion Brix3000 helps effectively remove denatured teeth with less pain or sensitivity. The time required for caries removal was lowest in the rotary method and highest in the brix3000 group, while the volume of caries removed was the lowest for brix3000 and highest for the rotary group.